2018
DOI: 10.1039/c7dt03689b
|View full text |Cite
|
Sign up to set email alerts
|

Addition of azomethine ylides to carbon-encapsulated iron nanoparticles

Abstract: The Prato reaction was applied for the covalent introduction of a variety of organic moieties onto carbon-encapsulated iron nanoparticles. The developed method is versatile and employs a broad range of commercially available reactants, including both aromatic and aliphatic aldehydes. The reported functionalization route provides high functionalization yields (ca. 12-21 wt%).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 37 publications
(33 reference statements)
0
7
0
Order By: Relevance
“…The first weight loss up to 110 °C is related to the presence of moisture in the studied sample. The next weight loss, which starts at 120 °C and is completed at 500 °C, is associated with the presence of the organic moieties attached to CEINs ,,,. Please note that the latter weight loss is not observed for the pristine CEINs.…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…The first weight loss up to 110 °C is related to the presence of moisture in the studied sample. The next weight loss, which starts at 120 °C and is completed at 500 °C, is associated with the presence of the organic moieties attached to CEINs ,,,. Please note that the latter weight loss is not observed for the pristine CEINs.…”
Section: Resultsmentioning
confidence: 96%
“…On a contrary, a dark‐green supernatant was observed for material 10 (Figure , c). This shows that Fc + was formed, and Fc was released from its inclusion complex with βCD . 5‐Fluorouracil (5‐FU) was then complexed inside the as‐formed “free” βCD's inner cavity.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It should be noted that the materials differ in the type of linker between the CEINs and Fc as well as in content of the Fc moiety (21.2, 16.3, and 6.3 wt % for CEINs-Fc-1 , CEINs-Fc-2 , and CEINs-Fc-3 , respectively). Importantly, cyclic voltammetry studies revealed the electrochemical activity of the nanoconjugates, as the fully reversible redox processes of the Fc ligand attached to CEINs were observed. It should be noted that transmission electron microscopy studies of various functionalized CEINs (including CEINs-Fc-2 ) revealed that the core–shell morphology of the obtained materials is retained after their surface modification, and no surface degradation after the functionalization is observed. ,,, …”
Section: Resultsmentioning
confidence: 96%
“…The structures of the materials (CEINs-Fc-1−CEINs-Fc-3) are presented in Figure 1. The materials were obtained via the one-step cycloaddition reaction (CEINs-Fc-1 47 and CEINs-Fc-2 48 ) or the three-step protocol (CEINs-Fc-3). 49 It should be noted that the materials differ in the type of linker between the CEINs and Fc as well as in content of the Fc moiety (21.2, 16.3, and 6.3 wt % for CEINs-Fc-1, CEINs-Fc-2, and CEINs-Fc-3, respectively).…”
Section: ■ Results and Discussionmentioning
confidence: 99%